Perilaku Pencarian Informasi Mahasiswa Jurusan Pendidikan Bahasa Indonesia Universitas Bung Hatta - Rannisa, Rayi; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis study aims to determine what information needs and how information seeking behavior of students of the Department of Indonesian Language Education at Bung Hatta University.Â The method used in this research is descriptive method with a qualitative approach. Data collection techniques were carried out by direct interviews with Indonesian Language Education Department students who were working on a thesis in the room of the Bung Hatta University Library thesis based on the interview grid provided by using a tool in the form of a Vivo Y83 pen as a tool. interview recorder.Â Based on the results of the study it can be concluded as follows. First, students of the Indonesian Language Education Department need information sources such as research journals, books, resource persons, and the internet in tracing information by considering the publication year. the collections in the Bung Hatta University library can be categorized as incomplete. Second, Indonesian Language Education Department students will seek information in other university libraries, and the Regional Library if the information needed cannot be found at the Bung Hatta University Library and visit the reading room and thesis room in information retrieval. OPAC Information Search tool (Online Public Access Catalog) has been used well in information retrieval at the Bung Hatta University Library so that the time needed to search for information can be shortened, namely 1 to 2 hours. Before searching for information, informants will record what things will be traced so that the information found can be used and according to needs.Keywords: information needs, information seeking behavior